Visual Cryptography Using Binary Amplitude-Only Holograms - Zhou, Lina; Xiao, Yin; Pan, Zilan; Cao, Yonggui; Chen, Wen (Frontiers in Photonics, 2022)
Visual cryptography (VC) is developed to be a promising approach to encoding secret information using pixel expansion rules. The useful information can be directly rendered based on human vision without the usage of decryption algorithms. However, many VC schemes cannot withstand occlusion attacks. In this paper, a new VC scheme is proposed using binary amplitude-only holograms (AOHs) generated by a modified Gerchberg-Saxton algorithm (MGSA). During the encryption, a secret image is divided into a group of unrecognizable and mutually-unrelated shares, and then the generated shares are further converted to binary AOHs using the MGSA. During image extraction, binary AOHs are logically superimposed to form a stacked hologram, and then the secret image can be extracted from the stacked hologram. Different from conventional VC schemes, the proposed VC scheme converts a secret image into binary AOHs. Due to the redundancy of the generated binary AOHs, the proposed method is numerically and experimentally verified to be feasible and effective, and possesses high robustness against occlusion attacks.